Soil Fertility Mapping using GIS in Three Agro-climatic Zones of Belgaum District, Karnataka - and S.P. Wani, K. Prabhavati, G.S. Dasog, P.L. Patil, K.L. Sahrawat (Journal of the Indian Society of Soil Science, 2015)
Soil fertility parameters viz., pH, electrical conductivity (EC), available macro- and micronutrients were determined in soil samples drawn at 300 m grid intervals from three micro-watersheds representing northern dry zone (zone-3), northern transition zone (zone-8) and hilly zone (zone-9) across a climatic gradient in Belgaum district of Karnataka. Based on the data maps were prepared in GIS environment using Arc GIS v 10.0. The soil fertility parameters clearly reflect the agro-climatic conditions under which the soils are formed. Soils of zone-3 were alkaline (pH> 8.5), soils of zone-8 slightly alkaline (7.0-8.5) and those of zone-9 slightly acidic (5.5-6.5). Whereas carbon and available nitrogen (N) in soils of both zone-3 and zone-8 were low, organic carbon (OC) was high (6.9 g kg-1) but the available N was medium (412 kg ha-1) in soils of zone-9. Available phosphorus (P) remained low in zones-3 and zone-8 but was marginally medium in zone-9. The available potassium (K) status of zone-3 soils was high (401 kg ha-1) but was medium in zone-8 and zone-9. Available sulphur (S) was low, DTPA extractable Zn and Fe was deficient, and Mn and Cu was sufficient in soils of both zone-3 and zone-8. In zone-9, however, available S and Zn were marginally sufficient but Fe, Mn and Cu were distinctly sufficient. In conformity with mean values described above, OC, available N, P, S and Zn were low (100% area for each) and available K was high in 91.2% area in soils of zone-3. Similarly for zone-8, OC and available N was low in 2/3 of area, available P was low in 76.5% area, available K was medium in 92.0% area, and low in available S (10%), deficient in Zn (99.1% area) and Fe (100% area). In agreement with means a large area under high OC (66.2%) and medium in available N (81.2%) and low in P (71.7%) was reflected in maps of zone-9. However, available K, S and Zn were distributed equally between low and medium classes despite K being medium and S being low and Zn being sufficient suggesting maps are preferred over means. The pH was slightly lower, OC and available N distinctly higher, and available P and DTPA extractable Cu lower in forest lands compared to agricultural lands in zone-9. Land use did not influence available K and DTPA extractable Zn, Fe and Mn.